2014
DOI: 10.1124/jpet.114.217331
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Hemorrhagic Shock-Induced Intestinal Barrier Dysfunction by Treatment with Diphenyldihaloketones EF24 and CLEFMA

Abstract: Gut is very sensitive to hypoperfusion and hypoxia, and deranged gastrointestinal barrier is implicated in systemic failure of various organs. We recently demonstrated that diphenyldihaloketone EF24 [3,5-bis(2-fluorobenzylidene)piperidin-4-one] improves survival in a rat model of hemorrhagic shock. In this study, we tested EF24 and its other analog CLEFMA (4-[3,5-bis(2-chlorobenzylidene)-4-oxo-piperidine-1-yl]-4-oxo-2-butenoic acid) for their effect on intestinal barrier dysfunction in hypovolemic shock. Hypov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Gut barrier dysfunction is known to trigger SIRS and cerebral damage (Grenz et al 2012, Hsieh et al 2011, Moore et al 2004, Rhodes et al 1973, Zhou et al 2012). This hypothesis is also supported by our recent report where we showed that EF24 prevents gut barrier dysfunction and this effect was associated with rapid accumulation of EF24 in the intestinal tissue (Yadav et al 2014a). Interestingly, brain tissue accumulates negligible amounts of administered EF24 (Lagisetty et al 2012).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Gut barrier dysfunction is known to trigger SIRS and cerebral damage (Grenz et al 2012, Hsieh et al 2011, Moore et al 2004, Rhodes et al 1973, Zhou et al 2012). This hypothesis is also supported by our recent report where we showed that EF24 prevents gut barrier dysfunction and this effect was associated with rapid accumulation of EF24 in the intestinal tissue (Yadav et al 2014a). Interestingly, brain tissue accumulates negligible amounts of administered EF24 (Lagisetty et al 2012).…”
Section: Discussionsupporting
confidence: 81%
“…The leading cause of SIRS is the loss of gut barrier function because of ischemic injury to the gut epithelium (Moore et al 2004, Grenz et al 2012, Rhodes et al 1973) which has also been implicated in brain dysfunction (Hsieh et al 2011, Zhou et al 2012). In previous reports, we described that an anti-inflammatory molecule EF24 exerts a pro-survival effect in a rat model of 50% hemorrhagic shock (Yadav et al 2014a, Yadav et al 2013) by preventing gut injury. In this work, we investigated the effect of EF24 on brain energy crisis caused by hemorrhagic shock in the same model.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Any untoward effect of a resuscitation fluid on the complement system has a potential to further complicate the pathology of shock, because the complement system also contributes to the SIRS (Szebeni et al, 2003). By virtue of their non-phospholipid nature, the HDAS-lipids reduce the complement activation induced by the liposome particles (Nag et al, 2013; Yadav et al, 2014). …”
Section: Discussionmentioning
confidence: 99%